Chapter Measuring urban inequalities. Spatial patterns of service access in sixteenth-century Leiden - van Steensel, Arie (Datini Studies in Economic History, 2020)
This contribution develops a broader understanding of well-being in premodern towns and by using digital methods to map social and economic inequalities, thereby drawing on insights from research on socio-spatial equity from urban studies. The key questions are how socio-economic inequality was reflected in the urban social topography and to what extent these spatial patterns reproduced inequality. Taking sixteenth-century Leiden as a case study, the spatial patterns of economic inequality and social segregation in this town are first examined. Next, the level of location-based inequality is explored by mapping and calculating urban spatial patterns of service accessibility.